Saint John of Avila: A priestly life shaped by the Crucified - Fernández Cordero, María Jesús (Razón y fe, 2018)
In the Apostolic Letter proclaiming Saint John of Avila a Doctor of the Universal Church, Benedict XVI emphasizes «the primacy of grace which makes us do what is right, the promotion of the spirituality centered in a reliance and the universal call to holiness lived as a response of God’s love»; as central points of his teaching and as ultimate reason of his mission and doctorate. This study provides the keys to his spirituality and his apostolic vocation while going over his itinerant and apostolic biography.